2022
DOI: 10.1177/10775595211064207
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment and Substance Use: A Behavior Genetic Analysis

Abstract: Child maltreatment is a pervasive social problem often perpetuated by family members and is related to a wide array of negative life outcomes. Although substance use is an outcome commonly associated with experiences of child maltreatment, not all individuals who experience maltreatment struggle with such issues. Many individuals can positively adapt to experiences of maltreatment based on levels of resilience and susceptibility. Research suggests that genetic differences may partly explain why negative outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Was this caused by "nature or nurture?" Azimi and Connolly (2022) studied the extent to which genetic and environmental factors influence the longitudinal association between child maltreatment and varying forms of substance use by analyzing a sample of twins from the National Longitudinal Study of Adolescent to Adult Health. They found that associations over time between cigarette and marijuana use and maltreatment were accounted for by both additive genetic and nonshared environmental factors.…”
Section: Children With Medical Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Was this caused by "nature or nurture?" Azimi and Connolly (2022) studied the extent to which genetic and environmental factors influence the longitudinal association between child maltreatment and varying forms of substance use by analyzing a sample of twins from the National Longitudinal Study of Adolescent to Adult Health. They found that associations over time between cigarette and marijuana use and maltreatment were accounted for by both additive genetic and nonshared environmental factors.…”
Section: Children With Medical Complexitymentioning
confidence: 99%
“…Austin et al (2022) identified 30 studies in a review that examined the association of child maltreatment with prenatal exposure to cocaine, alcohol, opioids, marijuana, amphetamines, and multiple substances, finding that substance-exposed infants had an increased likelihood compared to unexposed infants for child protective services involvement, maternal self-reported risk of maltreatment behaviors, hospitalizations and clinic visits for suspected maltreatment, and adolescent retrospective self-report of maltreatment. Was this caused by “nature or nurture?” Azimi and Connolly (2022) studied the extent to which genetic and environmental factors influence the longitudinal association between child maltreatment and varying forms of substance use by analyzing a sample of twins from the National Longitudinal Study of Adolescent to Adult Health. They found that associations over time between cigarette and marijuana use and maltreatment were accounted for by both additive genetic and nonshared environmental factors.…”
Section: Prenatal Substance Exposurementioning
confidence: 99%
“…In addiction research, child maltreatment and genetic factors have been linked to cigarette and marijuana use (Azimi & Connolly, 2022), and ACEs have accounted for issues with illicit drug use in one-half to two-thirds of cases (Dube et al, 2003). A modeling study showed that more than half of heroin and crack cocaine use was tied to ACEs (Bellis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%